Recent advances in flexible electrochromic devices : prerequisites, challenges, and prospects - Eh, Alice Lee-Sie (2020)
Electrochromic (EC) technology has progressed tremendously in recent years. Rigid EC devices have advanced to offer additional attractive physical attributes such as flexibility, stretchability, and foldability. These features are appealing for wearable and futuristic technologies, and hence serve to revolutionize EC applications toward deformable electronics. In this review, the essential prerequisites of each component of the flexible EC devices are delineated, such that each component is mechanically flexible to maintain the structural integrity of the device. The recent progress in flexible EC performance is discussed, from flexible to stretchable and the foldable device being the latest trend in deformable electronics. Next, we address the pertinent challenges often encountered in the fabrication of flexible EC devices and outline the adopted strategies from the literature to this point. Finally, the concept of the multifunctional EC device is discussed for achieving versatile emerging applications. We envision that this review will shed light on the properties of flexible ECs and shape the new milestones to be set for realizing a more versatile multifunctional EC device.